HUKUM EKONOMI SEBAGAI PANGLIMA PEMBANGUNAN - Purwanto Purwanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The law is supreme that must be obeyed by every citizen and must be upheld by the State in the context of national, state and community life. The constitutional foundation provides an understanding that the administration of the Indonesian State is based on the concept of law. The role of law in the reform era in all fields of science is concrete evidence, essentially the life of the community requires a set of legal rules that can always maintain order and furthermore provide legal certainty, usefulness and justice. The problem to be discussed in this paper the author wants to know